Acute focal infections of dental origin. (June 2014) - Olsen, Ingar; van Winkelhoff, Arie J.
Abstract: This article describes the most important pus‐producing acute oral infections (dental infections) that can spread extra‐orally. Most of these infections are spread by bacteria entering the bloodstream. However, dental infections have a number of other pathways for dissemination. By forming abscesses or phlegmon they can reach facial spaces that communicate with each other and then spread downwards to the mediastinum or upwards to the brain. In such cases dental infections can become, if not properly treated, life‐threatening. It seems that early diagnosis and treatment are imperative, and potentially infectious foci should be traced and eliminated. Dental hygiene and prophylaxis to prevent dental biofilm formation are important measures to reduce the risk of these calamities. The more compromised the host defense is, the more importance should be put on these measures. Although commensal bacteria are often involved in these infections, attention should also be paid to specific periodontal pathogens, and a proper microbial diagnosis, obtained using molecular methods plus bacterial sensitivity testing, can provide the patient with optimal care. Drainage of pus must be established where possible so that the optimal effect of antibiotics can be achieved. Penicillin is still the drug of first choice in settings where suspicion of methicillin‐resistant Staphylococcus aureus is low.